Pemanfaatan Lingkungan Pesisir Sebagai Sumber Belajar Dalam Merdeka Belajar : Pemanfaatan Lingkungan Pesisir Sebagai Sumber Belajar Dalam Merdeka Belajar - Mane, Azmin; Ihsyaluddin; Sahira (Jurnal Sains dan Pendidikan Biologi, 2022)
Merdeka Learning is a policy of the minister of education and culture that aims to encourage students to master various sciences to enter the world of work. This Independent Learning Policy is in accordance with Permendikbud No. 3 of 2020 concerning National Higher Education Standards. The purpose of this study was to determine how the use of the coastal environment as a source of learning in independent learning. The method in this study uses a descriptive qualitative approach by making students as research subjects. The source of this research data is in the form of journals related to the use of the coastal environment as a learning resource. Data collection techniques using listening and note-taking techniques. The results showed that the use of the coastal environment as a learning resource can provide opportunities for students to increase enthusiasm and motivation in understanding science and gain direct experience in the learning process outside the classroom. The purpose of the utilization pattern is so that students can more easily understand science in utilizing learning in the surrounding environment.Keywords: Environment, Learning Resources, Independent Learning